The role of early visual areas in human working memory - Xing, Yue (2014)
Evidence from recent studies suggested that visual areas (V1-V3) might be also actively involved in visually remembered features. The work presented in this thesis extended to other visual attributes, including motion coherence and contrast, with more detailed psychophysical and neuroimaging evidences to support the role of early visual areas in human visual working memory. The mnemonic characteristics of those visual traits were explored from temporal and spatial aspects using conventional psychophysical and functional brain imaging. Along the temporal domain, our results support the multi-channel theory that models the process occurred in early visual cortex when different visual features were perceived. In addition, experiments with “memory masking” procedures indicate that these ongoing representations show specificity of stimuli. Besides answering the question of whether early visual cortex was engaged in VWM, we also addressed the issue of how visual information is processed and held in these areas. We revealed that the visual system might exploit the “image-like” representation to discriminate stimuli with different contrasts, rather than only extracting and retaining the luminance differences. With the advent of up-to-date imaging technology, we also used Magnetic Resonance Imaging (MRI) to investigate the neural correlates of visual WM of contrast in human brain. In addition to the conventional fMRI analysis, we executed multivariate pattern analysis (MVPA), which allows more precise understandings of the structure and neural mechanism of WM. By using MVPA, we confirmed our previous psychophysical results. Along the spatial domain, this thesis provides further evidence of behaviour and brain activity when stimuli were displayed in different hemifields. Our findings showed the extra time and information cost when information relating the contrast of a stimulus was transmitted across hemispheres. Moreover, we unravelled the effect of spatial attention on primary visual cortex while visual features at different spatial locations were processed and memorized.